Simple Predictive Tool Estimates Sodium Adsorption Ratio for Evaluation of Potential Infiltration Problems using Reclaimed Wastewater - Bahadori, Alireza; Al-Haddabi, M.; Vuthaluru, Hari (Taylor & Francis Inc., 2012)
The physical and chemical characteristics of irrigation water are of particular importance. Sodium (Na) is one of the most problematic ions; when present in excessive concentrations it causes specific toxicity. In addition, another indirect effect of high Na content is the deterioration of the physical condition of soil such as formation of crusts, water logging, and reduced soil permeability. If the infiltration rate is greatly reduced, it may be impossible to supply the crop or landscape plant with sufficient water for good growth. In this work, a simple predictive tool, which is easier than existing approaches and requires fewer computations, is formulated to accurately predict the Na adsorption ratio as a function of concentrations of Na+, magnesium (Mg2+), and calcium (Ca2+); salinity of applied water; and the ratio of bicarbonate (HCO-3) over Ca2+ for interpretations of water quality for irrigation. The proposed method showed consistently accurate results for salinity of applied water up to 8 dS m−1 and ratio of HCO-3 over Ca2+ up to 20. Predictions showed an excellent agreement with the reported data with average absolute deviation of less than 3%. This proposed simple-to-use approach can be of immense practical value for engineers and scientists who need quick checks on Na adsorption ratio at a wide range of conditions without the necessity of any time-consuming experimental runs. In particular, soil scientists and agricultural engineers would find the proposed approach to be user friendly because it involves transparent calculations with no complex expressions.